Taiwan's Strategic Narrative: The Frontline Defender of Democracy Against Authoritarianism - Ermylina, Eva (Global Strategis, 2025)
This article discusses how Taiwan strategically crafts a narrative portraying Taiwan as the frontline defender of democratic and freedom values in the confrontation between liberal order and authoritarianism in the current debate of the international system. In facing a direct threat from the authoritarian regime, China, Taiwan has utilized this issue as a card to enhance global visibility, by compelling stories indicating Taiwan is the ‘’beacon of democracy’’ together with the United States and calling for a like-minded partner. This article applies strategic narrative framework on three levels namely issue, identity, and international system. This article argues that by portraying Taiwan as the core actor in safeguarding democracy, Taiwan intends to secure its international sphere through strategically enhancing its appeal by emphasizing Taiwan as the core actor in current geopolitical changing and acting as the norm-guardian to protect the established liberal order, advocate, and convince the global community of the importance of democratic and freedom values in facing authoritarianism.  Keywords: Cross-Strait Relations, International Recognition, Soft Power, United States-Taiwan-China Relations Artikel ini membahas tentang bagaimana Taiwan secara strategis membentuk sebuah narasi yang menggambarkan Taiwan sebagai pembela demokrasi dan nilai-nilai kebebasan terdepan di tengah konfrontasi antara tatanan liberal dan otoriter, yang mana menjadi perdebatan hangat dalam sistem internasional. Dalam menghadapi tantangan langsung dari rezim otoriter, yakni Tiongkok, Taiwan telah memanfaatkan isu ini sebagai kartu utama untuk meningkatkan visibilitasnya di tingkat global. Taiwan membentuk narasi yang meyakinkan sebagai “mercusuar demokrasi” bersama dengan Amerika Serikat, sekaligus mengajak terbentuknya kemitraan dengan negara-negara yang sehaluan. Artikel ini mengaplikasikan kerangka analisis narasi strategis pada tiga tingkat yakni isu, identitas, dan sistem internasional. Artikel ini berargumentasi bahwa dengan menggambarkan Taiwan sebagai aktor utama dan terdepan dalam menjaga demokrasi, Taiwan berupaya untuk memperkuat posisinya di ranah internasional melalui peningkatan citra positif. Upaya tersebut dilakukan dengan menekankan peran Taiwan sebagai penjaga norma yang melindungi tatanan internasional liberal, serta mengadvokasi dan meyakinkan komunitas global akan pentingnya mempertahankan nilai-nilai kebebasan dan demokrasi dalam menghadapi bangkitnya otoritarianisme. Kata-kata Kunci: Hubungan Lintas-Selat, Pengakuan Internasional, Soft Power, Hubungan Amerika Serikat-Taiwan-Tiongkok